Chemical composition of Callistemon citrinus (Curtis) Skeels aerial part essential oil and its pharmacological applications, neurodegenerative inhibitory, and genotoxic efficiencies. Issue 7 (24th May 2021) - Gogoi, Roktim; Begum, Twahira; Sarma, Neelav; Kumar Pandey, Sudin; Lal, Mohan
Abstract: Callistemon citrinus aerial part essential oil (CCEO) was analyzed for chemical compositions using GC/MS. Pharmacological activities such as neurodegenerative inhibitory, antioxidant, anti‐inflammatory, antimicrobial, and acetylcholinesterase activities were evaluated using the standard methodologies. Genotoxicity was investigated using Allium cepa assay. GC/MS analysis identified 27 compounds; eucalyptol (55.40%) was the major component. Radical scavenging activity showed IC50 value of 16.71 μg/mL. Protein denaturation assay showed IC50 value of 21.19 μg/mL and 19.53μg/mL in protease inhibitor activity. MIC assay revealed antimicrobial potential of CCEO against microbial strains B. cereus at 2.00 mg/mL, S. typhimurium at 4.50 mg/mL, S. mutans at 2.50 mg/mL, C. albicans at 4.00 mg/mL, and S . cerevisiae at 4.50 mg/mL concentrations. Mitotic index value (MI) of CCEO showed negligible genotoxicity with MI 17.25% close to distilled water 18.22%. Acetylcholinesterase strong inhibitory activity of CCEO was observed from IC50 = 6.335 μg/mL. CCEO could be a cheap and easy source for the extraction of the pure compound eucalyptol and possess various biological activities which increase its pharmacological value as well as its applicability in the field of flavor and fragrance industries. Practical applications: Eucalyptol is the major component of many pharmaceutical and food/flavor industries. The present investigation provides a new source for the isolation of pure compound eucalyptol in cost‐effective way. Additionally, the essential oil could also be used for the pharmaceutical formulation of antioxidant, inflammation inhibitory, and neurodegenerative inhibitory drug preparation under the safety range concentration. Abstract : The present investigation identified a natural source for easy isolation of pure compound eucalyptol. Pharmacological activity investigations revealed that Callistemon citrinus aerial part essential oil has the potential to be used in the formulation of antioxidant, inflammation inhibitory, and neurodegenerative inhibitory drugs. Genotoxicity study showed mitotic index value of 17.25% and chromosomal aberration of 4.0% by Callistemon citrinus aerial part essential oil, which is very close to distilled water mitotic index 18.22% and chromosomal aberration 2.0%.